The Impact of the Mandela-Castro Medical Collaboration Programme on Health Care Service Delivery in the Frances Baard District Hospitals in the Northern Cape Province - Motsumi, O.L; Van Niekerk, T (Administratio Publica, 2020)
Access to health care is a basic constitutional right in South Africa. The extreme shortage of doctors in sub-Saharan Africa is well documented, with 26 doctors per 100 000 people against a global average of 141 doctors per 100 000 people. The situation is no different in South Africa. The rural health care facilities have been facing a critical shortage of medical doctors where approximately 43% of the people in the rural areas often face greater health challenges such as having access to a mere 12% of the medical workforce in South Africa. In an attempt to address the shortage of doctors the late Presidents of South Africa and Cuba, Nelson Mandela and Fidel Castro, signed a bilateral agreement in 1996. One of the key terms of the agreement was to address the critical shortage of medical doctors in South Africa. This article reflects the findings of a study that was conducted to assess whether the Mandela-Castro Medical Collaboration Programme (MCMCP) has assisted in promoting health care service delivery in the small district hospitals in the Frances Baard District Municipality (FBDM) area in the Northern Cape Province. The period reviewed was from 2017 to 2019 because the doctors produced through the MCMCP had already been delivering health care services in hospitals of the FBDM. The research approach applied was deductive in nature and used quantitative data to generate propositions. The article provides insight into the impact of MCMCP on health care service delivery in the FBDM district hospitals, Northern Cape Province.
Research Article